1993
DOI: 10.1126/science.8420006
|View full text |Cite
|
Sign up to set email alerts
|

Blood-Brain Barrier Penetration and in Vivo Activity of an NGF Conjugate

Abstract: Nerve growth factor (NGF) is essential for the survival of both peripheral ganglion cells and central cholinergic neurons of the basal forebrain. The accelerated loss of central cholinergic neurons during Alzheimer's disease may be a determinant of dementia in these patients and may therefore suggest a therapeutic role for NGF. However, NGF does not significantly penetrate the blood-brain barrier, which makes its clinical utility dependent on invasive neurosurgical procedures. When conjugated to an antibody to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
110
0
1

Year Published

1993
1993
2011
2011

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 290 publications
(111 citation statements)
references
References 38 publications
0
110
0
1
Order By: Relevance
“…Since one of the major limitations in the use of NGF in brain pathologies is its large molecular size and its difficulty in crossing the blood-brain barrier, it was recently suggested that, for its utilization, NGF could be conjugated to transferrin receptor antibody (52), or, altertiatively, that one could use pharmacologic agents that act on brain NGFproducing cells (53). It is also possible that drugs which stimulate the release of NGF produced by resident cells, including MC, may be used to enhance the level of NGF in pathologies associated with the low availability of NGF.…”
Section: Ngf and The Nervous Systemmentioning
confidence: 99%
“…Since one of the major limitations in the use of NGF in brain pathologies is its large molecular size and its difficulty in crossing the blood-brain barrier, it was recently suggested that, for its utilization, NGF could be conjugated to transferrin receptor antibody (52), or, altertiatively, that one could use pharmacologic agents that act on brain NGFproducing cells (53). It is also possible that drugs which stimulate the release of NGF produced by resident cells, including MC, may be used to enhance the level of NGF in pathologies associated with the low availability of NGF.…”
Section: Ngf and The Nervous Systemmentioning
confidence: 99%
“…Transcranial focused ultrasound (FUS) has been shown to transiently-enhance the permeability of the BBB and permit antibodies, and probably other macromolecules into the intrathecal space (Jordão et al, 2010). Early interest in conjugation of NGF to transferrin or transferrin antibodies as a means of transport across the BBB (Friden et al, 1993;Liao et al, 2001) seems to have waned and shifted toward using this means of cellular uptake for anticancer or diabetic drugs. Gene therapy presents the most-advanced, current means of delivering NGF in a cerebral region-specific manner (Lad et al, 2003a;Nagahara & Tuszynski, 2011).…”
Section: Alzheimer's Disease -Treatment Strategiesmentioning
confidence: 99%
“…Some transport systems/sites that have been targeted include the LNAA, 64 receptor-mediated endocytosis/transcytosis, [65][66][67][68] and adsorptive endocytosis/transcytosis. 69,70 For the purpose of this review, we will focus on two favored methods for improving brain delivery, the use of vectors and glycosylation.…”
Section: Strategies To Improve Peptide Drug Bioavailability To the Brainmentioning
confidence: 99%